Pengaruh kondisi internal, kondisi debitur dan kondisi lingkungan terhadap strategi pemberian kredit dengan variabel mediasi Non Performing Loans (NPL) (Studi Kasus Bank Mandiri KCP Jambi Mendalo) - Rizki Handayani, Rury (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This research aims to determine and analyze the influence of internal conditions, debtor conditions, and environmental conditions on the lending strategy with NPL as a mediating variable. The population of this research included all customers with the sampling technique used was the Slovin formula so that the sample taken was 95 customers. The analysis technique used is to use multiple regression and path analysis. The result of this research showed that partially, internal conditions significantly affected the number of loans, debtor conditions and environmental conditions did not significantly affect the numberof loans and had a significant positive effect on non-performing loans (NPL). Internal conditions, debtor conditions and environmental conditions significantly influence non-performing loans (NPL). Internal conditions, debtor conditions and environmental conditions and the amount of credit simultaneously influence the non-performing loans (NPL). The amount of credit has an effect as an intervening variable internal conditions to NPL. The amount of credit has no effect as an intervening variable on the condition of the debtor and environmental conditions on non-performing loans.